Gender differentiated adaptation strategies considering climate risk perceptions, impacts and socio-technical conditions in Senegal’s dry regions - Kumar, Shalander; Pramanik, Soumitra; Yessofou, Adjani Nourou-Dine; Das, Abhishek; Singaraju, Niyati; Puskur, Ranjitha; Gondwe, Therese; Worou, Omonlola Nadine; Huyer, Sophia (International Crops Research Institute for the Semi-Arid Tropics, 2023)
This study analyses the gender-differentiated farmers’ perception of climate risk and its impact, access to climate information, and adaptation strategies with the aim to develop gender responsive climate adaptation pathways in Senegal’s dry regions. Study used data collected from 514 farm households through primary survey between May and June 2022 covering Kaffrine, Louga, and Thies sub-regions and multiple communes, including 5% women headed households and 12% women respondents. Through several interactions with key stakeholders, it became evident that while both men and women hold similar perceptions regarding climate risk and its impact on farming systems, women possess significantly less access to Climate Information Services (CIS) and Climate Smart Agriculture (CSA) technologies. The women farmers were found to be much more vulnerable to climate risks but often they rely on traditional coping mechanisms such as non-farm income through cottage activities, home gardening etc. rather than modern CSA technologies. Both men and women emphasized the importance of context-specific climate information to be shared with them. Barriers to climate adaptation, such as limited knowledge of CSA, inadequate resources, and dearth of timely climate information, were identified, underscoring the importance for community resilience. The Tobit regression analysis highlighted multifaceted determinants of households’ ability to adapt to climate change, emphasizing the roles of gender empowerment, education, access to CSA and CIS, and regional disparities. The study underscores the importance of understanding community perceptions and drivers of adaptive capacity, addressing barriers, and based on empirical evidence we propose a gender-responsive pathway to climate-resilient agriculture. These insights and proposed pathways can help policymakers and practitioners to navigate the complex terrain of climate change effectively. Finally, these findings underscore the need for informed policy interventions, tailored strategies and appropriate institutional interventions to address cultural barriers and enhance women’s role in farming decision making and access to CIS and CSA.